Presentasi Diri dalam Kencan Online pada Situs dan Aplikasi Setipe dan Tinder - Widya Permata Sari; Rina Sari Kusuma (MediaTor (Jurnal Komunikasi), 2018)
Online dating is one forms of Computer Mediated Communication (CMC) where the participants aren’t required to do a Face-to-Face communication to communicate with each other. By this limitation, online dating users get the chance to present themselves with selective self-presentation such as only present the good sides of themselves and even present themselves innacuratedly in order to appear as ideal figure. This research wants to know how online dating users present themselves to their online partners and do they do the hyperpersonal communication, in the form of selective self-presentation . This research uses descriptive-qualitative methods with semistructure interview as data collecting method. The samples who were interviewed in this research are five people who join the online dating site and mobile application setipe.com and Tinder. All five samples were selected by snowball sampling method. By using qualitative content analysis as data analysing technique, this research found that online dating users do selective self-presentation where they will choose which things they want to present to their online partners, eventhough they are being honest and present themselves accuratedly. Online dating users do it to get a pleasant communication with their online partners also to anticipate the possibility of meeting their partners offline (in real life).